DESIGN AND IMPLEMENTATION OF WATER FLOW AND POWER SUPPLY SYSTEMS FOR CATFISH AND TILAPIA SEEDS COUNTER - Fathin Madani Rochaka, M.
This document explains the design and implementation of the water flow system and power supply system that will be used in the automatic catfish and tilapia seed counter. The aim of creating this system is to help count large numbers of catfish and tilapia seeds in a short time, and have high accuracy. This design was carried out by calculating a good slope so that the device could count 30,000 fish seeds/hour. The dimensions of the device are 67.5 cm × 37 cm × 50.2 cm. Apart from that, the power supply system is also designed so that all components used can receive resources according to their needs without experiencing a shortage or excess of power. The results of the development of the flow and power supply system show that the implementation of Newton's second law and one-dimensional motion with constant acceleration on the counter path, as well as an integrated circuit using a 12V 20A adapter, relay, DC-DC step down, and Li-ion battery as a backup supply can meet throughput of 42 seeds/3.68 seconds for catfish seeds, 42 seeds/4.06 seconds for tilapia seeds, and the tool can operate well without power shortages.